Statistical Modeling of Environmental Factors on Microbial Urea Hydrolysis Process for Biocement Production - Hamed Khodadadi Tirkolaei; Huriye Bilsel (Advances in Materials Science and Engineering)
Calcium carbonate is a widely used raw material by many industries. It can be precipitated through microbial process within soil pores as cementitious bonding agent between grains for geotechnical applications. It is called microbially induced calcium carbonate precipitation (MICP). Designing an appropriate biogrout material for injection into soil is essential for controlling the amount, type, time, and place of the biocement production within pores. For this purpose, understanding the active reactions and the kinetics of bacterial growth and urea hydrolysis is necessary. A conductometric method and spectrophotometry were used in this study to, respectively, monitor the urea hydrolysis reaction progress and bacterial growth in S. pasteurii-inoculated urea-NB-NH4Cl solution at different level of the environmental factors that are initial cell concentration, urea concentration, and temperature. Variation in conductivity of the solution versus logarithmic scale of time was depicted as microbial ureolysis characteristic curve (MUCC) through which lag duration, specific rate, and potential of urea hydrolysis at each condition were obtained. Central composite face-centered (CCF) design, which is one of the response surface methodologies, was employed to statistically fit polynomial models explaining the bacterial growth and the characteristics obtained from MUCCs in terms of the environmental factors and their interactions. An optimization analysis based on the urea-normalized responses was also carried out.